Review Penelitian Teknologi Informasi, Komunikasi dan Covid 19 menggunakan teknik Bibliometrik - Komalasari, Rita; Munawar, Zen; Putri, Novianti Indah (Jurnal ICT : Information Communication & Technology, 2021)
The covid-19 pandemic around the world has a huge impact on all sides of people's lives, prompting many researchers to create research topics and publish them in journals. This study aims to analyze research topics in relation to information and communication technology during the Covid-19 pandemic using bibliometric analysis. The data is obtained through article search on Scopus database, the topic area used is the criteria of title, keywords and abstract articles related to information and communication technology and Covid-19 which is used as a reference for metadata search. Bibliometric analysis results are obtained based on the VosViewer visualization. The number of open access journal articles sourced from the Scopus database in 2020 is 130 and in 2021 it is 29, the search was conducted on March 7, 2021. The country that publishes the most articles is the United States, while the keywords covid, pandemic, technology and studies are the keywords that appear most often in research. The use of VosViewer is intended to analyze the relationship of The Covid keyword with the technology used during the pandemic as a topic of research area. This research is expected to be a reference for further research in order to explore the topic of research on technology during the Covid-19 pandemic that has not existed before.